Dicing Up MicroRNA Gene Expression Profiles in Normal and Neoplastic Smooth Muscle Cells - Miano, Joseph M. (American Society for Investigative Pathology, 2010)
This Commentary discusses the role of miRNA expression profiles in identifying malignancy.